Targeted Drug Therapy for Senescent Cells Alleviates Unilateral Ureteral Obstruction-Induced Renal Injury in Rats - Ting Li; Kexin Yang; Yinghao Tong; Shangze Guo; Wei Gao; Xiangyu Zou (MDPI AG, 2024)
Hydronephrosis resulting from unilateral ureteral obstruction (UUO) is a common cause of renal injury, often progressing to late-stage renal fibrosis or even potential renal failure. Renal injury and repair processes are accompanied by changes in cellular senescence phenotypes. However, the mechanism is poorly understood. The purpose of this study is to clarify the changes in senescence phenotype at different time points in renal disease caused by UUO and to further investigate whether eliminating senescent cells using the anti-senescence drug ABT263 could attenuate UUO-induced renal disease. Specifically, renal tissues were collected from established UUO rat models on days 1, 2, 7, and 14. The extent of renal tissue injury and fibrosis in rats was assessed using histological examination, serum creatinine, and blood urea nitrogen levels. The apoptotic and proliferative capacities of renal tissues and phenotypic changes in cellular senescence were evaluated. After the intervention of the anti-senescence drug ABT263, the cellular senescence as well as tissue damage changes were re-assessed. We found that before the drug intervention, the UUO rats showed significantly declined renal function, accompanied by renal tubular injury, increased inflammatory response, and oxidative stress, alongside aggravated cellular senescence. Meanwhile, after the treatment with ABT263, the rats had a significantly lower number of senescent cells, attenuated renal tubular injury and apoptosis, enhanced proliferation, reduced oxidative stress and inflammation, improved renal function, and markedly inhibited fibrosis. This suggests that the use of the anti-senescence drug ABT263 to eliminate senescent cells can effectively attenuate UUO-induced renal injury. This highlights the critical role of cellular senescence in the transformation of acute injury into chronic fibrosis.